2022
DOI: 10.3390/polym14194014
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Based Healable 2K PU Textile Coating for Durable Applications

Abstract: A biobased healable 2K polyurethane (PU) coating incorporating a Schiff base was synthesized and applied as a thin coating on textiles. The Schiff base, made out of cystine and vanillin, contained reversible imine and disulfide bonds and was used as a chain extender in PU synthesis. The FT-IR analysis indicated the successful incorporation of the Schiff base in the PU backbone. Compared with control PU coatings, the healable bio-based PU coating with the Schiff base showed very good healing properties using he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The main applications of PU and PUR are coatings (PU or PUR), sealants (PU or PUR), adhesives (PUR), elastomers (PU), and foams (PUR) [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main applications of PU and PUR are coatings (PU or PUR), sealants (PU or PUR), adhesives (PUR), elastomers (PU), and foams (PUR) [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Anwar Jahid et al reported different types of shape-memory polyurethane coatings for cotton fabrics with remarkable water resistance and permeability properties for sportswear [ 41 , 42 ]. David De Smet et al reported several types of polyurethane formulations as a waterproof coating for polyester textiles [ 36 , 43 ]. N. Raman Dhineshbabu et al developed PUR coatings containing iron titanate nanoparticles for UV shielding [ 39 ].…”
Section: Introductionmentioning
confidence: 99%